LEGAL CERTAINTY IN COLLECTION OF VALUE ADDED TAX ON TRADE TRANSACTIONS THROUGH THE ELECTRONIC SYSTEM (PAYPAL CASE STUDY) - Dewi, Berliana Chandra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Legal certainty in the collection of value added tax on trade transactions through an electronic system that guarantees conformity between the application of tax provisions and their statutory regulations. And with the results of this writing, it has been shown that the provision of taxation of value added tax and sales tax on luxury goods for PMSE transactions is not a new type of tax. That trade transactions by PMSE business actors that are illegal will be detrimental to both parties who use the digital platform for trade transactions, as well as losses in terms of state revenue in the form of taxes.